2022
DOI: 10.5194/hess-26-6247-2022
|View full text |Cite
|
Sign up to set email alerts
|

Poor correlation between large-scale environmental flow violations and freshwater biodiversity: implications for water resource management and the freshwater planetary boundary

Abstract: Abstract. The freshwater ecosystems around the world are degrading, such that maintaining environmental flow1 (EF) in river networks is critical to their preservation. The relationship between streamflow alterations (subsequent EF violations2) and the freshwater biodiversity response is well established at the scale of stream reaches or small basins (∼<100 km2). However, it is unclear if this relationship is robust at larger scales, even though there are large-scale initiatives to legalize the EF requiremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Another critical issue is that few studies have tried to link the water PB across different scales; specifically, the following two issues are not well resolved: (a) the connections among local water PBs, as most studies used local data without considering its connectivity with other regions, and (b) the impact of local water-PB transgressions at large scales, as no previous studies have investigated how local water-PB transgressions could trigger a water-PB transgression at a larger scale or at the global scale. However, Mohan et al (2022) found poor relationship between EWF-biodiversity at large scales, even though it is well established at small scales, implying the need for a holistic approach for water PB research across different scales. Recently, Zipper et al (2020) proposed a novel framework to address the challenge associated with mismatched control variables between the global and local scales, but the above two issues are still not well-resolved in a quantitative way.…”
Section: Assessments At Different Scalesmentioning
confidence: 89%
See 3 more Smart Citations
“…Another critical issue is that few studies have tried to link the water PB across different scales; specifically, the following two issues are not well resolved: (a) the connections among local water PBs, as most studies used local data without considering its connectivity with other regions, and (b) the impact of local water-PB transgressions at large scales, as no previous studies have investigated how local water-PB transgressions could trigger a water-PB transgression at a larger scale or at the global scale. However, Mohan et al (2022) found poor relationship between EWF-biodiversity at large scales, even though it is well established at small scales, implying the need for a holistic approach for water PB research across different scales. Recently, Zipper et al (2020) proposed a novel framework to address the challenge associated with mismatched control variables between the global and local scales, but the above two issues are still not well-resolved in a quantitative way.…”
Section: Assessments At Different Scalesmentioning
confidence: 89%
“…The seasonal variation of water flow rate (e.g., flood flow) and the mismatch between the water supply and human water demand can result in a portion of unused water resources. Second, the control‐response relationship between freshwater biodiversity and EWF has not been well represented in the determination of EWF (Mohan et al., 2022), which further challenges the quantification of water PB based on EWF. Third, there is a large uncertainty in runoff estimates derived through multiple global hydrological models (GHMs), which would propagate into the estimation of EWF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impacts of streamflow depletion on aquatic ecosystems may be through direct changes in streamflow or indirectly through changes in water quality or temperature caused by depletion, as in the case of salmonids which are highly dependent on cool groundwater inflows (Larsen & Woelfle-Erskine, 2018) and are a major driver of policy and management decisions in many settings (Lackey, 1999). While a variety of approaches to estimate environmental flow needs for aquatic ecosystems have been developed and proposed, these are not well-correlated with freshwater biodiversity (Mohan et al, 2022), suggesting that more information beyond just changes in water quantity is needed to link streamflow depletion to adverse ecological outcomes (Lapides et al, 2022;Yarnell et al, 2020). While recent studies have identified low-flow signatures as most sensitive to streamflow depletion across diverse hydrologic regions (Lapides et al, 2023), links between hydrologic change and ecological outcomes have predominantly been local (Liu et al, 2020;Perkin et al, 2017).…”
Section: Decision Support Steps: Identify Decision Need(s) and Decisi...mentioning
confidence: 99%